PENGARUH PEMBELAJARAN INKUIRI TERBIMBING BERBASIS PhET SIMULATION TERHADAP KEMAMPUAN BERPIKIR REFLEKTIF SISWA MATERI CAHAYA DAN SIFATNYA KELAS V SD - Putri Dita Galih Pramesthi; Rosmiati; Triman Juniarso (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low learning outcomes and reflective thinking skills of 5th-grade students on the topic of Light and Its Properties. Reflective thinking has never been implemented at SD Negeri Tembok Dukuh IV/86 Surabaya. Observations revealed that the science scores in Class VA and Class VB for this topic were still low. This study aims to examine the impact of the Guided Inquiry learning model using PhET Simulation on students' reflective thinking skills and to measure the improvement of these skills after applying the model. The research employs a quantitative descriptive method, with subjects from Class VA (25 students) and Class VB (24 students) in the odd semester of the 2024/2025 academic year. Data collection was done through observations, written tests, questionnaires, and documentation. The results show a significant improvement in students' learning outcomes after the implementation of this learning model. Additionally, students demonstrated enhanced reflective thinking skills, particularly in the areas of habitual action, understanding, reflection, and critical reflection. In conclusion, the Guided Inquiry learning model using PhET Simulation is effective in improving students' learning outcomes and reflective thinking skills on the topic of Light and Its Properties. This model also encourages a more interactive, engaging, and relevant learning experience for students.